Effects of two different sealer material on fiber post bond strength in root canal - Kurniawaty Kurniawaty; Christine A. Rovani; Juni J. Nugroho; Nurhayaty Natsir; Indrya K. Mattulada (DiscoverSys Inc., 2016)
This study was aimed to determine the effect of epoxy resin-based and MTA-based sealer on fiber post bond strength in the root canal wall.Samples are mandibulary first premolar, with a single root canal. They are divided into three groups: negative control group which is a gutta percha obturation without sealer, gutta percha obturation with epoxy resin based sealer [AH Plus], and gutta percha obturation with MTA-based sealer [MTA Fillapex] groups. Samples were decoronated, prepared, obturated and then stored in the incubator at room temperature for one week, the post space were prepared for fiber post insertion. Samples were mounted in the PVC pipes before insertion. Samples were stored in the incubator for one day before bond strength testing. Universal testing machine was used with the speed of 0,5 mm/minutes. Data were collected and analysed using ANOVA.The result showed that the fiber post bond strength in the root canal obturated with epoxy resin-based sealer was higher [12.311 N/mm2] than MTA-based sealer [10.786 N/mm2], but that result was not statistically significant. Therefore, it was concluded that the root canal obturated with epoxy resin-based sealer did not yield a significant bond strength [p = 0.689] compared to MTA-based sealer [p> 0.05].